2007
DOI: 10.1136/tc.2006.019505
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, quitting and mortality in an elderly cohort of 56 000 Hong Kong Chinese

Abstract: In old age, smoking continues to be a major cause of death, and quitting is beneficial. Smoking cessation is urgently needed in rapidly ageing populations in the East.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 29 publications
(19 reference statements)
4
51
0
5
Order By: Relevance
“…After full-text evaluation, 16 articles were selected that provided information from 34 cohorts on sex differences in the association between smoking and stroke in the general population (Table). 5,6,15,16,[25][26][27][28][29][30][31][32][33][34][35] These data were extended with data from ARIC, 18 NHANES III, 19 APCSC, 20 and SHHEC, 21 adding a further 47 cohorts. Baseline characteristics of all 81 cohorts included in this study are described in the Table. Overall, data on 3 980 359 individuals were available, in whom ≥42 401 fatal and nonfatal strokes were documented (1 study, including 56 167 individuals, did not report the number of stroke events).…”
Section: Resultsmentioning
confidence: 99%
“…After full-text evaluation, 16 articles were selected that provided information from 34 cohorts on sex differences in the association between smoking and stroke in the general population (Table). 5,6,15,16,[25][26][27][28][29][30][31][32][33][34][35] These data were extended with data from ARIC, 18 NHANES III, 19 APCSC, 20 and SHHEC, 21 adding a further 47 cohorts. Baseline characteristics of all 81 cohorts included in this study are described in the Table. Overall, data on 3 980 359 individuals were available, in whom ≥42 401 fatal and nonfatal strokes were documented (1 study, including 56 167 individuals, did not report the number of stroke events).…”
Section: Resultsmentioning
confidence: 99%
“…Study participants were all aged o60 yrs, follow-up was generally short, and only one recent study was large (56,167 subjects). All studies showed that COPD mortality rates were higher in ex-than never-and current smokers, but the large cohort study from elderly health centres in Hong Kong followed for 3.2-5.0 yrs found that RRs of all-cause mortality in ex-smokers lay between those of never-and current smokers [54].…”
Section: Clinically Based Studiesmentioning
confidence: 99%
“…Chinese studies There are few mortality studies from China [51][52][53][54], and all are population-based. There are no studies addressing COPD morbidity.…”
Section: Clinically Based Studiesmentioning
confidence: 99%
“…Keil et al 2006). A newer case-control-study of Hong Kong-Chinese older than 65 years showed that tobacco abstinence is still beneficial at higher ages ("Quitting is beneficial") (Lam et al 2007). Surveys showed that approximately 70 % of all smokers would like to quit smoking and over 40 % have already tried at least once.…”
Section: Smokingmentioning
confidence: 99%